Performance anixety among dancers and associations with perfectionism - Lilja Rúriksdóttir 1991- (2024)
The present study investigated performance anxiety among ballet and modern dancers and associations with two types of perfectionistic tendencies. Sixty-four (n = 64) dancers from Iceland, The United States, The United Kingdom, Canada, Germany, Belgium, Sweden, Denmark, Norway, The Netherlands and Switzerland originally participated. The majority of participants were female (71%). The mean for performance anxiety (M = 11.9, SD = 5.16) was similar to the diagnostic criteria value of The Mazzarolo Music Performance Anxiety Scale that is estimated at 11.0. A functional analysis of variance revealed that maladaptive perfectionism (evaluative concerns) predicted performance anxiety F(15) = 2.38, p = 0.01 while adaptive perfectionism (strivings) was unrelated to performance anxiety. Additionally, the background variables gender and age were not related to performance anxiety while an increase in dancing experience positively predicted performance anxiety F(1) = 4.87, p = 0.033. Results indicated that performance anxiety had a moderate positive correlation with the maladaptive type of perfectionism r (59) = .39, p = .002. Study limitations and the potential of Acceptance and Commitment Therapy based interventions are discussed. Keywords: dance, performance, state anxiety, perfectionism, sport Þessi rannsókn kannaði frammistöðukvíða á meðal ballett- og samtímadansara og tengsl við tvær tegundir af fullkomnunaráráttu. Sextíu og fjórir (N = 64) dansarar frá Íslandi, Bandaríkjunum, Englandi, Kanada, Þýskalandi, Belgíu, Svíþjóð, Danmörku, Noregi, Hollandi og Sviss tóku þátt. Meirihluti þátttakenda voru konur (71%). Meðaltalið fyrir frammistöðukvíða (M = 11.9, sf = 5.16) var svipað og klíníska gildið á skalanum sem ber heitið The Mazzarolo Music Performance Anxiety Scale sem áætlað er um 11.0. Fjölþátta dreifigreining leiddi í ljós að neikvæð fullkomnunarárátta spáði fyrir um frammistöðukvíða F(15) = 2.38, p = 0.01 á meðan jákvæð fullkomnunarárátta var ótengd frammistöðukvíða. Bakgrunnsbreyturnar kyn og aldur voru ...